Self-Mixing Interferometer Based on Frequency Analysis Method for Accurate Refractive Index Measurement - Yongbing Zhang; Yingbin Wei; Chenxi Chen; Wencai Huang; Xiulin Wang; Huizhen Xu (IEEE Photonics Journal)
A new method based on self-mixing interference (SMI) for refractive index measurement by means of simply frequency analysis is proposed. The optical phase shift is implemented by translating a transparent object through a motorized stage with a setting velocity. Then, the refractive index is determined by the frequency of SMI fringes. A relative repeatability of refractive index estimated in $1.0× 10^{-4}$ is achieved experimentally. This method has found that there exists an optimal velocity to achieve minimum error of refractive index measurement.